2016
DOI: 10.1093/biomet/asw025
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian view of doubly robust causal inference: Table 1.

Abstract: In causal inference confounding may be controlled either through regression adjustment in an outcome model, or through propensity score adjustment or inverse probability of treatment weighting, or both. The latter approaches, which are based on modelling of the treatment assignment mechanism and their doubly robust extensions have been difficult to motivate using formal Bayesian arguments; in principle, for likelihood-based inferences, the treatment assignment model can play no part in inferences concerning th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…Another source of uncertainty is structural uncertainty arising from model misspecification that produces biased estimates of relative effect, although it can be reduced using doubly robust estimation. Alternatively, it might be possible to incorporate external information to mitigate this or take a Bayesian perspective . Generating joint posterior distributions about parameters should be seen as an important aim in HTA to properly represent uncertainty about inputs to decision analytic models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another source of uncertainty is structural uncertainty arising from model misspecification that produces biased estimates of relative effect, although it can be reduced using doubly robust estimation. Alternatively, it might be possible to incorporate external information to mitigate this or take a Bayesian perspective . Generating joint posterior distributions about parameters should be seen as an important aim in HTA to properly represent uncertainty about inputs to decision analytic models.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it might be possible to incorporate external information to mitigate this or take a Bayesian perspective. 78 Generating joint posterior distributions about parameters should be seen as an important aim in HTA to properly represent uncertainty about inputs to decision analytic models.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized proportions of partial nephrectomies shown here were calculated using the truncated and normalized weights, with the standard errors estimated using the bootstrap. Since the bootstrap can easily produce further positivity violations when refitting the multinomial logistic assignment model in the bootstrap resamples, we made use of the Bayesian analogue that uses continuous‐valued Dirichlet distributed sampling weights instead 46 . The reference level of care in both plots is the overall proportion of partial nephrectomies in the province.…”
Section: Illustrationmentioning
confidence: 99%
“…The second equality above follows from the connection between the predictive distributions under the experimental and observational representations. This connection arises through the importance sampling identity …”
Section: A Bayesian Weighting Estimator Of the Attmentioning
confidence: 99%
“…Thus, this particular two‐step approach is neither proper Bayesian nor does it result in good frequentist properties. Second, it was shown that the point estimator does not possess good small‐sample properties . Kaplan and Chen also examined the differences in the causal estimate when incorporating noninformative versus informative priors in a model averaging stage .…”
Section: Introductionmentioning
confidence: 99%